2007
DOI: 10.1074/jbc.m701166200
|View full text |Cite
|
Sign up to set email alerts
|

An Archaeal Protein with Homology to the Eukaryotic Translation Initiation Factor 5A Shows Ribonucleolytic Activity

Abstract: To identify proteins that are involved in RNA degradation and processing in Halobacterium sp. NRC-1, we purified proteins with RNA-degrading activity by classical biochemical techniques. One of these proteins showed strong homology to the eukaryotic initiation factor 5A (eIF-5A) and was accordingly named archaeal initiation factor 5A (aIF-5A). Eukaryotic IF-5A is known to be involved in mRNA turnover and to bind RNA. Hypusination of eIF-5A is required for sequencespecific binding of RNA. This unique post-trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 57 publications
1
29
0
3
Order By: Relevance
“…litchfieldiae , several proteins associated with RNA degradation (Levy et al ., ; Hou et al ., ) also had higher abundance at low temperature: ribonuclease J (halTADL_2415) and the RNA‐binding DnaG protein (halTADL_0764). This extended to an archaeal homolog of eukaryotic initiation factor 5A (halTADL_2262) for which the precise function in RNA turnover is unclear, although the C‐terminal region is structurally similar to the RNA chaperone CspA (Wagner and Klug, ). For Hrr.…”
Section: Resultsmentioning
confidence: 99%
“…litchfieldiae , several proteins associated with RNA degradation (Levy et al ., ; Hou et al ., ) also had higher abundance at low temperature: ribonuclease J (halTADL_2415) and the RNA‐binding DnaG protein (halTADL_0764). This extended to an archaeal homolog of eukaryotic initiation factor 5A (halTADL_2262) for which the precise function in RNA turnover is unclear, although the C‐terminal region is structurally similar to the RNA chaperone CspA (Wagner and Klug, ). For Hrr.…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that divalent cations are not required for their activity, and they were capable of cleaving yeast tRNA (Fusi et al, 1993;Shehi et al, 2001). A homologue of the eukaryotic initiation factor 5A (eIF-5A) called archaeal initiation factor 5A (aIF-5A), from Halobacterium salinarum, was also described as an RNase with activity in low salt concentrations without addition of MgCl 2 (Wagner & Klug, 2007). Furthermore, two different dehydrogenases were identified in the same organism, with RNase III-like properties and cleavage patterns dependent on MgCl 2 : an aspartate-semialdehyde dehydrogenase and acyl-CoA dehydrogenase (Evguenieva-Hackenberg et al, 2002).…”
Section: Other Endonucleasesmentioning
confidence: 99%
“…Hypusine is essential for activity of eIF5A/aIF5A (including that of Hbt. salinarum ), now considered important in translation elongation (Wagner and Klug, 2007; Saini et al, 2009; Park et al, 2010). In hypusine modification of eIF5A, deoxyhypusine synthase (DHS) transfers a 4-aminobutyl moiety from spermidine to the ε-amino group of the conserved lysine residue to form a dexoxyhypusine intermediate, which is hydroxylated to a hypusine residue by deoxyhypusine hydroxylase (DOHH) (Fig.…”
Section: Hypusine Modificationmentioning
confidence: 99%
“…[Ne-(4-amino-2-hydroxybutyl)-L-lysine] is formed upon PTM of a conserved lysine residue and is found only in eukaryotic translation 'initiation' factor 5A (eIF5A) and the related archaeal aIF5A (Park et al, 1981(Park et al, , 2010Schumann & Klink, 1989;Bartig et al, 1992). Hypusine is essential for the activity of eIF5A/aIF5A (including that of H. salinarum), now considered important in translation elongation (Wagner & Klug, 2007;Saini et al, 2009;Park et al, 2010). In hypusine modification of eIF5A, deoxyhypusine synthase (DHS) transfers a 4-aminobutyl moiety from spermidine to the e-amino group of the conserved lysine residue to form a dexoxyhypusine intermediate, which is hydroxylated to a hypusine residue by deoxyhypusine hydroxylase (DOHH) (Fig.…”
Section: Hypusinementioning
confidence: 99%